Consumer Satisfaction Analysis of Jihan Brownies Cake in Kuantan Tengah District, Kuantan Singingi Regency - Tari Seskiya; Jamalludin Jamalludin; Chezy WM Vermila (Baselang, 2021)
The purpose of this study was to determine consumer behavior towards brownies cakes, to determine consumer satisfaction with brownies cake product in the district of Kuantan Tengah. The method used in this study is the likert scale and the method of analysis of Important and Performance Analysis (IPA) and Consumers Satisfaction Index (CSI) or consumer satisfaction index. Based on the result of the research, the result of consumer behavior towards brownies are in the very satisfied category with the number of 20 lives of 30 respondenst with a percentage of 100%. From the result of the calculation of brownies cakes as a whole the value of the consumer satisfaction index is 69,50%. Wher this value is in the range 50% - 75% consumer satisfaction index. Based on the result of CSI as a whole are in the satisfied category, what is meant here is price, hygiene, aroma, packaging, taste, texture, and color.